TEKNOLOGI KECERDASAN BUATAN, BIG DATA ANALYSIS, DAN INTERNET OF THINGS: POTENSI DAN PERANNYA DALAM PENANGANAN COVID-19 DI INDONESIA - Syahrul Mubaroq; Inas Mufidatul Insyiroh (Jurnal Kependudukan Indonesia, 2020)
Coronavirus Disease 2019 (COVID-19) has spread throughout the world including Indonesia. The poor prevention and treatment of the initial phase results in a continuing increase in the number of positive cases and mortality caused by this virus. On the other hand, countries that have adopted policies that are fast and appropriate technology have been able to reduce the rate of additional cases and mortality rates. In this paper the authors conduct an analytical study of the application of technologies such as artificial intelligence, big data, and the internet of things in accelerating the detection, prevention, response, and recovery of COVID-19 cases in several countries and their possibilities to be applied in Indonesia. The authors suggest the Indonesian government to apply appropriate policies and technologies to reduce the high growth of COVID-19 cases.